2014
DOI: 10.7567/jjap.53.09pa16
|View full text |Cite
|
Sign up to set email alerts
|

Bulk photovoltaic effect in a BiFeO3thin film on a SrTiO3substrate

Abstract: Epitaxial BiFeO 3 (BFO) thin films with striped-and single-domain structures have been grown on SrTiO 3 (STO) ( 103) and ( 113) substrates by radiofrequency planar magnetron sputtering. The domain structure of BFO was controlled by the orientation of the STO substrate. Piezoelectric force microscopy revealed that BFO thin films on STO (103) and STO (113) had a striped-domain structure with 71°domain walls running along o010p STO , and a single-domain structure, respectively. To confirm the photovoltaic propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…The growth details are found in the Experimental Section; here, we just point out that solution‐processing fabrication is relatively simple and readily up‐scalable for photovoltaic cell manufacturing . Short exposure time to high temperature during the solution process helps preserve the integrity of the transparent bottom electrode, thus allowing the thin film device depicted in Figure to be fabricated in a vertical configuration, instead of the more usual lateral architecture . This allows the entire area of the device to be illuminated from below without any shadow effects.…”
mentioning
confidence: 99%
“…The growth details are found in the Experimental Section; here, we just point out that solution‐processing fabrication is relatively simple and readily up‐scalable for photovoltaic cell manufacturing . Short exposure time to high temperature during the solution process helps preserve the integrity of the transparent bottom electrode, thus allowing the thin film device depicted in Figure to be fabricated in a vertical configuration, instead of the more usual lateral architecture . This allows the entire area of the device to be illuminated from below without any shadow effects.…”
mentioning
confidence: 99%
“…Several studies have attempted to elucidate the various contributions to the photovoltaic response -bulk or otherwise -in ferroelectrics [15][16][17][18][19][20][21][22][23]. In particular, bismuth ferrite (BFO) has been found to generate significant bulk photocurrents; combined with its unusually low band gap of 2.7 eV, it has attracted a great deal of attention for its potential in photovoltaic applications [21,[23][24][25][26][27][28][29][30][31]. The understanding of the fundamental physics behind the effect has advanced as well; recently we demonstrated that the BPVE can be attributed to "shift currents", and that the bulk photocurrents may be calculated from first-principles.…”
mentioning
confidence: 99%
“…33 and 165 proposed a model regarding potential steps at domain walls as the driving force for charge separation (Fig. 184 Second, BFO thin films with periodic domain structures (both 71 o and 109 o domains), showed angular dependency of photocurrent on the incident light polarization. In the dark, a large electric field (~50 kV/cm) will be formed within the domain wall, and the potential step causes the offset of conduction band and valence band (Fig.…”
Section: Domain Wall Theorymentioning
confidence: 99%